(untitled) (Research, Society and Development, 2023)
The present study aimed to analyze the evidence available in the literature on the importance of containment measures used by the nursing team in emergency services for adults suffering from psychiatric disorders. This is an integrative literature review study with a qualitative and descriptive approach, carried out in March 2023. Fifty-seven studies were found indexed in the BVS, LILACS, PubMed, Scielo databases, obtained from the intersection between the descriptors, being included for review in a total of 11 articles. From the systematic search in the databases, 11 studies were included in total in order to fulfill the proposed objective with the characteristics referring to authorship and Year of publication, titles, journals, objectives, methodology and main results found. Therefore, the studies showed that the use of physical, chemical and mechanical restraints are important during assistance in preventing aggression to the team and patient (Self-Aggressiveness), as well as for relieving the symptoms of patients in a psychiatric outbreak admitted to the emergency room. Furthermore, it demonstrated that nursing professionals are not prepared to care for patients in mental distress, whether due to lack of training, fear and insecurity. Added to this, it demonstrated the fragility of the articulation of the mental health and emergency care networks that can significantly compromise the assistance to users of this nature. The importance of using containment in care is emphasized, but it is above all necessary to carry out a humanized approach based on qualified and welcoming listening so as not to worsen the health of patients.